(untitled) (Current Horticulture, 2024)
An experiment was conducted at Floriculture division of Horticulture Research Centre, BARI, Gazipur, during November 2019 - June 2021 to study the effect of management practices and bulb sizes on production of quality bulb and bulblets of lilium (Lilium sp.). Two management practices, viz. removal of spikes and without removal of spikes were considered as one factor and three bulb sizes, viz. large, medium and small as another factor in a randomized complete block design. Removal of spikes produced maximum number of bulbs and bulblets/plant (1.41 and 1.81, respectively), the heaviest and largest bulb (26.02g and 4.47cm) and bulblets/plant (6.88g). Large-sized bulbs produced maximum number of bulbs and bulblets/plant (1.51 and 1.98, respectively), heaviest and largest bulb (27.80g and 4.67cm, respectively) and bulblets/plant (7.92g). The removal of spikes produced longest plant (52.58 cm), spike (64.05 cm), rachis (22.18 cm) and bud (8.69 cm) and largest bud and floret (2.80 and 16.96 cm, respectively) and maximum number of florets/stick (4.78) from bulbs obtained during first year. Considering various levels of bulb sizes, large-sized bulbs produced longest plant (53.77 cm), spike (67.22 cm), rachis (23.17 cm) and bud (8.86 cm) and largest bud and florets (2.86 and 17.14 cm, respectively) and maximum number of florets/stick (5.11) from bulbs obtained during the first year. Similarly, removal of spikes and large-sized bulbs produced a good number of bulbs and bulblets during second year from bulbs obtained during the first year. Large-sized bulbs combined with removal of spikes produced quality bulbs as well as flowers.